MULTIFACTOR PRIMARY PREVENTION OF ISCHEMIC HEART DISEASE IN MIDDLE-AGED MEN AND ITS EFFICACY (10-YEAR FOLLOW-UP) - A. M. Kalinina (Столичная издательская компания, 2015)
Aim. To evaluate in a prospective 10-year follow-up study cardiovascular mortality rate in a population of middle-aged men with different levels of total cardiovascular risk, and correlation between combinations of risk factors (RF) and the extent of coronary atherosclerosis according to autopsy reports of subjects who have died of ischemic heart disease (IHD) undiagnosed during life-time. To estimate the efficacy of multifactor primary prevention.Material and methods. The analysis was based on the results of the "Multifactor ischemic heart disease prevention" prospective controlled study of two 40-59-year-old men populations (1preventive measures, 2 - a group of comparison). Standardized epidemiological examination using unified protocol was performed in the total of 6656 people. The article presents results of prospective follow-up of the two groups, participants of which did not initially have  IHD clinical signs: the group 1 - n=2975, the group 2 - n=2705. Active correction of IHD RF (high blood pressure, hypercholesterolemia, overweight, smoking, low physical activity) in the group 1 lasted for 5 years; the whole period of follow-up was 15 years. At that, end points (all-cause mortality, myocardial infarction and stroke) were estimated and verified in each case. This article evaluates the 10-year follow-up period.Results. Prevention in middle-aged men population allowed significantly to reduce levels of the major RF and total cardiovascular risk by 38.1%. In the absence of preventive measures cardiovascular risk, predicted by the SCORE chart, already realizes during the first 5 years. In fact cardiovascular mortality rates during 10-year follow-up exceed the risk predicted by the SCORE chart. Active primary IHD prevention allows to reduce the risk of cardiovascular death in men with initially high risk - by 36.9% and with initially very high risk - by 43.4%. Men, who have died of IHD undiagnosed during life-time, with combination of 3 and more RF revealed coronary artery stenosis of multiple localization in 91.7%, with 2 RF - in 89.6% and with singular RF - in 78.3% of the cases.Conclusion. We proved substantiated the relevance of multifactor primary prevention of atherosclerosis-mediated cardiovascular diseases. Primary medical prevention has demonstrated its effectiveness, especially at high cardiovascular risk, and particularly evident at a long-term follow-up. For the first time ever long-term prospective follow-up study of the population with standardized assessment of health parameters revealed negative predictive value of multiple RF in respect to coronary atherosclerotic lesions estimated postmortem.